2017
DOI: 10.18632/oncotarget.15318
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulation of long non-coding RNA PlncRNA-1 promotes proliferation and induces epithelial-mesenchymal transition in prostate cancer

Abstract: ObjectiveTo confirm that PlncRNA-1 regulates the cell cycle in prostate cancer cells and induces epithelial-mesenchymal transition (EMT) in prostate cancer through the TGF-β1 pathway.ResultsPlncRNA-1 and TGF-β1 expression levels were significantly higher in prostate cancer tissues than in normal prostate tissues (P < 0.05) and were significantly positively correlated. TGF-β1, N-cadherin and Cyclin-D1 were downregulated and E-Cadherin was upregulated in LNCAP cells after silencing of PlncRNA-1, as determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 32 publications
2
52
0
1
Order By: Relevance
“…TGF‐β1 has been demonstrated to associate with proliferation, differentiation and apoptosis of various cell types . Zhang et al indicated that small concentrations of TGF‐β1 promoted the proliferation of BMSCs via activation of Wnt/β‐catenin pathway Several studies have presented the regulatory effects of lncRNAs on the expressions of TGF‐β1 in breast cancer and prostate cancer cells . In this research, we conducted qRT‐PCR and Western blot to analyze the association between TGF‐β1 and LET.…”
Section: Discussionmentioning
confidence: 98%
“…TGF‐β1 has been demonstrated to associate with proliferation, differentiation and apoptosis of various cell types . Zhang et al indicated that small concentrations of TGF‐β1 promoted the proliferation of BMSCs via activation of Wnt/β‐catenin pathway Several studies have presented the regulatory effects of lncRNAs on the expressions of TGF‐β1 in breast cancer and prostate cancer cells . In this research, we conducted qRT‐PCR and Western blot to analyze the association between TGF‐β1 and LET.…”
Section: Discussionmentioning
confidence: 98%
“…LncRNAs have become a hot topic as diagnostic markers of diseases. The transcriptional level of PlncRNA-1 is signi cantly elevated in multiple malignancies, and PlncRNA-1 acts as a transcriptional regulator of various developmental processes [17][18][19][20][21][22][23][24][25]. In several human tumours, overexpression of PlncRNA-1 is related to poor OS, high TNM classi cation, advanced clinical stage, low histological differentiation, and poor vital status [20,22,24,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…PlncRNA-1 is ubiquitously expressed in the prostate, salivary glands and 25 other tissues. It has been shown that PlncRNA-1 plays an important role in various cancer types, including prostate cancer, colorectal cancer, osteosarcoma, glioma and oesophageal squamous carcinoma [17][18][19][20][21][22][23][24][25][26]. Accumulating evidence has demonstrated that PlncRNA-1 acts as a transcriptional regulator to modify various developmental processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we focused on understanding the underlying mechanism on how LINC00844 might control the expression of androgen-regulated genes. Previously, our lab and others have demonstrated that AR collaborative factors such as NKX3-1 [27] and lncRNAs like PlncRNA [33,34] act through a feed forward mechanism to regulate AR mRNA and protein levels to influence the expression of downstream AR target genes. Thus, we examined if LINC00844 could also function in a similar fashion.…”
Section: Linc00844 Regulates Ar Binding To Chromatinmentioning
confidence: 99%